2014
DOI: 10.1016/j.neuron.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Orbitofrontal and Lateral Prefrontal Cortices to Economic Choice and the Good-to-Action Transformation

Abstract: SUMMARY Previous work indicates that economic decisions can be made independently of the visuo-motor contingencies of the choice task (space of goods). However, the neuronal mechanisms through which the choice outcome (the chosen good) is transformed into a suitable action plan remain poorly understood. Here we show that neurons in lateral prefrontal cortex reflect the early stages of this good-to-action transformation. Monkeys chose between different juices. The experimental design dissociated in space and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
159
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 51 publications
17
159
1
Order By: Relevance
“…Previous work (Padoa-Schioppa andAssad, 2006, 2008) had already ruled out several possible variables (e.g., other value, value difference, total value, etc.) and found that variables offer value, chosen value, and chosen juice explained the vast majority of taskrelated neural responses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work (Padoa-Schioppa andAssad, 2006, 2008) had already ruled out several possible variables (e.g., other value, value difference, total value, etc.) and found that variables offer value, chosen value, and chosen juice explained the vast majority of taskrelated neural responses.…”
Section: Methodsmentioning
confidence: 99%
“…Future work shall examine this issue more directly. Importantly, neurons encoding the weighted choice could still provide the input to the good-toaction transformation (Cai and Padoa-Schioppa, 2014), because the activity of cells associated with the chosen juice, even if weighted by the probability, is still higher than the activity of cells associated with the other, nonchosen juice.…”
Section: Other Cell Groups and Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, monkey orbitofrontal neurons code the chosen value and map it onto action activity in dorsolateral prefrontal cortex to initiate the action ("good-to-action transformation," Ref. 81). …”
Section: Object Value Versus Action Valuementioning
confidence: 99%
“…Finally, neurons in parietal cortex, and possibly other areas involved in attention, signal the abstract value or importance of objects and individuals in the local environment, in order to shape the adaptive allocation of attention to others. Notably, current evidence suggests that social and non-social information remains segregated from perception through evaluation and may only be integrated during the process of making decisions and planning action ( [75]; but see [94]). These circuits provide the foundation upon which more complex social behaviours, like cooperation and alliance formation, are developed and elaborated.…”
Section: Mechanisms Mediating the Evaluation Of Social Partners' Valumentioning
confidence: 99%